2019
DOI: 10.1016/j.molcel.2019.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Condensin-Mediated Chromosome Folding and Internal Telomeres Drive Dicentric Severing by Cytokinesis

Abstract: Highlights d Rap1 and condensin promote dicentric breakage at telomere fusions d Condensin refolds stretched dicentric bridges prior to their breakage by septation d Breakage hotspots result from a higher chance of being entrapped at the abscission site d Rap1 bound in tandem with close spacing may stall condensin by steric hindrance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 86 publications
3
33
0
Order By: Relevance
“…This might explain why condensin did not accumulate at all RNAP3-transcribed genes in the absence of Sen1 (Fig 2). Our data are consistent with the observation that the number and density of DNA-bound Rap1 proteins influence condensin function in budding yeast (Guérin et al , 2019) and strengthen the idea that arrays of proteins that are tightly-bound to DNA could trigger the accumulation of condensin. Similarly, it is conceivable that a number of tightly-bound proteins (for example transcription factors or paused RNAP2 molecules) contribute to position condensin complexes in the 5’ of genes in mitosis in vertebrates (Sutani et al , 2015; Kim et al , 2013), even in the absence of significant transcriptional activity.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This might explain why condensin did not accumulate at all RNAP3-transcribed genes in the absence of Sen1 (Fig 2). Our data are consistent with the observation that the number and density of DNA-bound Rap1 proteins influence condensin function in budding yeast (Guérin et al , 2019) and strengthen the idea that arrays of proteins that are tightly-bound to DNA could trigger the accumulation of condensin. Similarly, it is conceivable that a number of tightly-bound proteins (for example transcription factors or paused RNAP2 molecules) contribute to position condensin complexes in the 5’ of genes in mitosis in vertebrates (Sutani et al , 2015; Kim et al , 2013), even in the absence of significant transcriptional activity.…”
Section: Resultssupporting
confidence: 91%
“…What could be the intrinsic properties of RNAP molecules in the 3’ end of genes that impact the position of condensin? We hypothesized that RNAP backtracking could be a contributing factor for two reasons: (i) RNAP molecules are often backtracked around termination sites (Sheridan et al , 2019; Lemay et al , 2014) and (ii) backtracking would conceivably strengthen the interaction of RNAP molecules with chromatin, making them less dynamic and possibly a harder obstacle to bypass by translocating condensin molecules (Guérin et al , 2019; Brandão et al , 2019). To test this hypothesis, we sought to prolong RNAP2 backtracking events by over-expressing a dominant-negative mutant of TFIIS ( tfs1D274AE275A in fission yeast (Lemay et al , 2014), thereafter referred to as tfs1DN ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…What could be the intrinsic properties of RNAP molecules in the 39 end of genes that impact the position of condensin? We hypothesized that RNAP backtracking could be a contributing factor for two reasons: (i) RNAP molecules are often backtracked around termination sites (Lemay et al, 2014;Sheridan et al, 2019) and (ii) backtracking would conceivably strengthen the interaction of RNAP molecules with chromatin, making them less dynamic and possibly a harder obstacle to bypass by translocating condensin molecules (Brandão et al, 2019;Guérin et al, 2019). To test this hypothesis, we sought to prolong RNAP2 backtracking events by over-expressing a dominant-negative mutant of TFIIS (tfs1D274AE275A in fission yeast [Lemay et al, 2014], thereafter referred to as tfs1DN).…”
Section: Resultsmentioning
confidence: 99%
“…Another fundamental question is to understand how chromatin and large DNA-bound protein assemblies impact the loop extrusion activity of condensin in vivo. Loop extrusion on chromatin in vivo is predicted to be roughly 10 times slower than on naked DNA in vitro , and it was recently suggested that arrays of proteins tightly bound to DNA could hinder the loop extrusion activity of condensin, possibly by constituting a steric obstacle to the reeling of chromatin (Guérin et al, 2019). An inability to bypass obstacles might result in the formation of unlooped chromatin gaps within mitotic chromosomes .…”
Section: Introductionmentioning
confidence: 99%